(untitled) (Research, Society and Development, 2022)
Objectives: to understand the meanings attributed by adolescents who presented/present the behaviour of self-mutilation of the body in adolescence, as well as to identify the implications of the effects on their involvement in daily activities. Specific objectives: understand the meaning of this behaviour for the subjects and identify the triggers that lead to self-mutilating behaviour. Methodology: this is a study with a qualitative approach and descriptive character, carried out with adolescents who practice or practice self-mutilation of the body during the period of adolescence. The collection was carried out through a semi-structured questionnaire in a virtual way, which had twelve questions covering different themes, including aspects related to feelings, senses, forms and effects arising from the self-mutilation of the body for the participant who experienced or experiences this experience in adolescence. Results: It was possible to notice that the motivation for the practice of self-mutilation can have several functions, such as expressing emotions, reducing negative feelings and anguish, and seeking relief from all these sensations, which ends up interfering with the involvement of adolescents in their daily activities, affecting their involvement in social, educational and domestic activities. Conclusion: it is observed that the role of the occupational therapist becomes relevant, as it provides care centered on the subject considering its uniqueness and potential, acting as a facilitator in the process of daily transformation.